Pediatric mandibular fracture therapy – A case report - Tušek, Ivan; Ilić, Miroslav P.; Tušek, Jasmina; Ivić, Stojan; Tušek, Branislav (Vojnosanitetski pregled, 2021)
Introduction. Frequency of pediatric mandibular fractures is relatively uncommon. Apart from rare exceptions, there is minimal invasive access in the treatment of those injuries in order to avoid the future developmental disorders. Case report. During the game with a colt, a 6-year-old boy was kicked by hoof in the chin. The child did not lose consciousness and did not experience nausea or vomiting. According to clinical examination and radiological analysis, diagnosis was assigned as dislocated mandibular fracture in the parasymphysis part of the jaw and luxation injury of teeth 31 and 72. The surgical treatment under general anesthesia encompassed reduction and bimanual manipulation of bone fragments up to the optimal restoration of the dental occlusion, along with osteosynthesis with titanium miniplates. Luxated deciduous tooth 72 at the fracture line was extracted and luxated permanent tooth 31 was fixed to tooth 41 with wire. The patient was given antibiotic therapy. Additional immobilization of the luxated tooth 31 and mandibular fracture was performed after surgery by composite resin splint. During five-month follow-up period there were no signs of pathological movements in the fracture line, no luxation of tooth 31 and no restriction in mouth opening. Conclusion. Osteosynthesis with miniplates is adequate and very efficient treatment method in dislocated mandibular fracture that is recommended in children with both deciduous and mixed dentition. It is necessary to remove miniplates after fracture consolidation.